Student’s experiential learning in implementing sulam through online and distance learning during COVID-19: a case study of advanced mind empowerment for success (minds) course - Md Kamal, Mahanijah (Universiti Teknologi MARA, Kedah, 2024)
Service-Learning Malaysia - University for Society or (SULAM) is an effective mechanism to produce holistic students. Through SULAM, teaching and learning (T&L) in the classroom is transform in the form of experiential learning to nurture the characteristics of soft skills such as leadership, critical thinking, creativity, communication and collaboration skills to students. In addition, through SULAM, students' motivation and confidence level can be nurture as part of the process towards lifelong learning experiences. Advanced Mind Empowerment for Success (MinDS) or HPD240 is one of the advanced courses under the leadership pillar that was first conducted via online for Mac 2021 academic session. The implementation of SULAM project is to produce a meaningful learning experience in an innovative way through the creativity of students in presenting their content with SULAM participants. Therefore, this paper study the perceptions of student’s ability in delivering a very good and interactive session with their participants. Hence, study their experiences while implementing and conducting SULAM through T&L environment of COVID-19 pandemic via online platform. The data used is in the form of a qualitative approach where SPSS is used for analysis purposes. Five elements of student experiences are studied which based on soft skills, perceptions, understanding, participations and MySkills. In this SULAM, 29 facilitators were involved with the participation of 173 participants through google meet medium. The results show that the five elements are quite significant with the experiential learning of students who implement SULAM with the role of facilitator.